Visnagin treatment attenuates DSS-induced colitis by regulating inflammation, oxidative, stress, and mucosal damage - Sravathi, Vemula; Doppalapudi, Madhuri; Yadala, Ravi Kumar; Banothu, Anilkumar; Anumolu, Vijaya Kumar; Veera, Hanuman Donga Durga; Debbarma, Bhaskar (Frontiers in Veterinary Science, 2025)
Ulcerative colitis (UC), is a chronic inflammatory bowel disease characterized by recurrent episodes of inflammation and ulceration of the colonic mucosa. This study aimed to explore the therapeutic potential effects of visnagin (VIS), a natural furanochromone using a murine model, focusing on tight junction protein expression, oxidative stress, apoptosis and associated inflammation in a dextran sodium sulfate (DSS) induced UC model. A total of 36 male C57BL/6 mice were divided randomly into six groups (n = 6): Group 1 served as the control, group 2, treated with DSS (2% with three 5-day cycles diluted in distilled water administered orally). Group 3 (VIS) perse alone (60 mg/kg b. wt), orally for 31 days, Group 4-low dose of VIS (30 mg/kg b. wt for 31 days with DSS, group 5-high dose VIS (60 mg/kg b. wt) for 31 days with DSS and Group 6 Dexamethasone sodium @ 1 mg/kg b. wt-IP with DSS for 31 days. Disease progression and therapeutic outcomes were assessed by monitoring clinical symptoms, body weight changes, colon length, Disease activity index (DAI), oxidative stress indices, gross and histopathological analysis, inflammatory cytokine levels and immunohistochemical expression. Results demonstrated that VIS co-administration, particularly at high doses, significantly mitigated DSS-induced weight loss, colon shortening. This protective effect was further supported by a significant reduction in oxidative and nitrosative stress which was evident from decreased levels of nitrite and Malondialdehyde (MDA) in VIS treated groups 4 and 5. Further, VIS suppressed pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, IFN-γ, NF-κB, IL-17, MPO and TGF-β) while increasing anti-inflammatory IL-10 levels in colon tissues. Reverse transcription polymerase chain reaction (RT-PCR) analysis revealed significantly reduced mRNA expression of TNF-α and IL-17 along with increased occludin expression in groups 4, 5 and 6. VIS also improves intestinal barrier by increasing the expression of tight junction occludin, as confirmed through RT-PCR. Immunohistochemical analysis showed strong positive immunoreactivity for NF-κB, COX-2, NLRP3 and TNF-α in DSS group, which wa notably reduced in VIS-treated groups. Additionally, VIS improved intestinalbarrier integrity by upregulating occluding expression. Histopathological analysis further confirmed that VIS attenuated DSS-induecdcolonic lesions. In conclusion, VIS exhibits potent anti-inflammatory and mucosal-protective properties, making it a promising therapeutic candidate for managing UC. Its ability to modulate inflammatory pathways and enhance intestinal barrier function suggests its potential as an alternative treatment for UC.